Shoot-out at Sugar Creek - Spillane, Mickey, 1918-2006; Collins, Max Allan (Spillane, Mickey, 1918-2006. Caleb York western, 2021)
"It starts with an abusive, drunken young scoundrel who resists arrest, holds a barmaid hostage, and gets what he deserves from the blazing .44 of Sheriff Caleb York. The New Mexico lawman doesn't regret taking such deadly action, but the late youth's powerful mother, cattle baroness Victoria Drummond, seems bound to feel differently. To York's surprise, Victoria takes the news with stoic resignation - all she asks of him is a favor: help her convince Willa Cullen - the love of Caleb's life - to sell her the spread that Willa's late father had carved out of the wilderness. Willa, every bit as strong-willed as her rival, refuses to give up her land without a fight. Sheriff York anticipates an ugly showdown brewing with himself in the dangerous middle. And before he can stop it from escalating, the seductive cattle queen sends an army of hired guns to Sugar Creek, the sole source of water available for Willa's herd. York finds himself caught in the crossfire of a savage shoot-out between Willa's cowboys and Victoria's gunfighters. No matter who wins, it's going to be a bloodbath. . ."--Publisher.